Chiral 2‐phenyl‐3‐hydroxypropyl esters as PKC‐alpha modulators: HPLC enantioseparation, NMR absolute configuration assignment, and molecular docking studies. Issue 3 (28th December 2021) - Linciano, Pasquale; Nasti, Rita; Listro, Roberta; Amadio, Marialaura; Pascale, Alessia; Potenza, Donatella; Vasile, Francesca; Minneci, Marco; Ann, Jihyae; Lee, Jeewoo; Zhou, Xiaoling; Mitchell, Gary A.; et al.
Abstract: Protein kinase C (PKC) isoforms play a pivotal role in the regulation of numerous cellular functions, making them extensively studied and highly attractive drug targets. In our previous work, we identified in racemate 1–2, based on the 2‐benzyl‐3‐hydroxypropyl ester scaffold, two new potent and promising PKCα and PKCδ ligands, targeting the C1 domain of these two kinases. Herein, we report the resolution of the racemates by enantioselective semi‐preparative HPLC. The attribution of the absolute configuration (AC) of homochirals 1 was performed by NMR, via methoxy‐α‐trifluoromethyl‐α‐phenylacetic acid derivatization (MTPA or Mosher's acid). Moreover, the match between the experimental and predicted electronic circular dichroism (ECD) spectra confirmed the assigned AC. These results proved that Mosher's esters can be properly exploited for the determination of the AC also for chiral primary alcohols. Lastly, homochiral 1 and 2 were assessed for binding affinity and functional activity against PKCα. No significative differences in the K i of the enantiopure compounds was observed, thus suggesting that chirality does not seem to play a significant role in targeting PKC C1 domain. These results are in accordance with the molecular docking studies performed using a new homology model for the human PKCαC1B domain. Abstract :